PERKEMBANGAN UMKM DI DALAM MAL (Study kasus Pempek Farina di dalam Solo Grand Mal) - Al Mursyid, Muhammad Hilaluddin; Admadja, Efrika Dwi; Muftiningtyas, Tiara (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2024)
Nowadays, shopping centers are not only for shopping, but also as places for culinary hunting. In the Solo Grand Mal shopping center there is a culinary outlet, namely Pempek Farina. This research was conducted with the aim of analyzing the development and marketing strategy of Pempek Farina MSMEs in the Solo Grand Mall. The method used by researchers is a qualitative method to gain in-depth understanding. The subjects of this research are MSMEs in Solo Grand Mall. This research data was obtained through interviews with MSME Pempek Farina employees, direct observation at the location, and analysis of consumer satisfaction with services at Pempek Farina. Researchers analyzed data using an interactive analysis approach. From the results of this research, it can be concluded that the development and marketing of Pempek Farina MSMEs at its inception in 1994, started from using carts and now has at least 40 outlets in Indonesia. The marketing strategy for Pempek Farina is usually carried out by the Marketing Team by holding promotions every month.